Strategies to Improve Understanding of the Impact of Promotions and Discounts on Purchase Decisions - Nurlaila, Nurlaila; Ramadhan, Naufal; Simanjuntak, Nicholas Faisal (Taqaddum: Community Service Journal, 2023)
This study trained the sample about the impact of promotions and discounts on consumer purchasing decisions via ShopeeFood, specifically among students in Medan. The research employs Deep Interview, Training, and Participatory methods to gather insights. In-depth interviews reveal consumer perceptions regarding how ShopeePay’s promotions and discounts influence their purchasing choices. Training sessions aimed to educate users on the effective use of ShopeePay and to enhance their awareness of security measures, while participatory methods involved practical usage of ShopeePay in ShopeeFood transactions. Results from a 15-day community service initiative with 150 consumers indicate that a significant number of users experience issues such as slow transaction processing, lack of awareness about promotions, and technical errors. Additionally, some users were unfamiliar with proper ShopeePay usage. Training effectively improved user knowledge, loyalty, and awareness of promotions, leading to more practical and satisfying transactions. The analysis demonstrates that discounts have a substantial impact on purchasing decisions, with a high coefficient value indicating that price reductions are directly proportional to increased purchase likelihood. Although promotions also play a role in attracting consumer attention, discounts are more influential due to their immediate and understandable financial benefits, ease of price comparison, and direct impact on consumer decisions.